2010
DOI: 10.1542/peds.2008-3086
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight and Lung Function in Adulthood: Retrospective Cohort Study in China, 1948–1996

Abstract: Low birth weight may increase the prevalence of and risk for low lung function in adulthood in the Chinese population. The development of lung function may be affected by hypogenesis in utero.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 30 publications
5
28
0
Order By: Relevance
“…Our results are consistent with previous studies that suggested that children with histories of not only LBW and pre-term birth, but also SGA, a synthetic indicator of birthweight and gestational age, had increased risks of allergic respiratory symptoms [13][14][15][16][17][18]32]. Impaired growth in utero, resulting in LBW and earlier gestational age, is associated with diminished surfactant activity and pulmonary cellularity, due to the fact that the lungs of immature neonates are not fully developed either anatomically or immunologically [13,[16][17][18].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with previous studies that suggested that children with histories of not only LBW and pre-term birth, but also SGA, a synthetic indicator of birthweight and gestational age, had increased risks of allergic respiratory symptoms [13][14][15][16][17][18]32]. Impaired growth in utero, resulting in LBW and earlier gestational age, is associated with diminished surfactant activity and pulmonary cellularity, due to the fact that the lungs of immature neonates are not fully developed either anatomically or immunologically [13,[16][17][18].…”
Section: Discussionsupporting
confidence: 92%
“…These studies suggest that the high mortality from COPD in low-income countries is associated with a low FVC and not obstruction, as has generally been assumed, and raises an important question over the origins of this low FVC. There is good evidence that low ventilatory function in later life is associated with low birthweight [5,[24][25][26][27] and possibly with early infections [4,5,28], and these conditions are associated with poverty [4,29,30]. However, COPD mortality appears to respond immediately to improvements in GNI, and it is therefore unlikely that the changes noted here are solely related to effects from poverty in early life.…”
Section: Discussionmentioning
confidence: 75%
“…All studies adjusted for age, sex and height, except for two that did not adjust for height. In particular, one study (24) did not adjust the association of FVC for height. Tables E8 and E9 show the effect estimates for FVC and FEV1/FVC, respectively, used in the sensitivity analyses that included adjustment for smoking.…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%